Quantitative assessment of systolic and diastolic function in patients with LGE negative systemic amyloidosis using CMR. (1st April 2017) - Kuetting, Daniel L.R.; Homsi, Rami; Sprinkart, Alois M.; Luetkens, Julian; Thomas, Daniel K.; Schild, Hans H.; Dabir, Darius
Abstract: Objectives: In clinical routine myocardial affection in amyloidosis is assessed by qualitative late gadolinium enhancement (LGE). Recent studies suggest that early cardiac involvement in amyloidosis may be overlooked by qualitative LGE assessment. The aim of this study was to assess possible early cardiac involvement in LGE negative AL patients by means of systolic and diastolic strain assessment and quantitative enhancement. Methods: 51 individuals (17 Patients with LGE positive light-chain amyloidosis (AL) (Group A), 17 Patients with LGE negative systemic AL (Group B), and 17 healthy controls (Group C)) were investigated. SSFP-Cine sequences were acquired in short axis slices as well as horizontal long axis views. Standard CMR parameters as well as Feature Tracking (FT) derived systolic and diastolic circumferential and longitudinal strain parameters were calculated. Additionally, contrast enhanced MRI images were analyzed to quantitatively determine the extent of enhancement. Results: AL patients with and without LGE both had significantly lower early diastolic strain rate (EDSR) values and peak systolic longitudinal strain (PSLS) values than healthy controls (EDSR: Group A 63.1 ± 17.6; Group B: 74.46 ± 11.8; Group C: 86.82 ± 12.7; F(2.48) = 10.7 p < 0.001); (PSLS: Group A: − 13.44 ± 1.9%; Group B: − 20.31 ± 1.2%; Group C: − 23.11 ± 1.4%; F(2.48) = 167.6; p < 0.001). Analysis of quantitative LGE enhancement revealed increased enhancement in qualitative LGE negative AL patients compared to healthy controls (Group A: 19.6 ± 8.9%; Group B: 8.2 ± 3.9%; Group C: 2.4 ± 1.3% F(2.48) = 52.2; p < 0.001). Conclusion: CMR strain analysis detects early systolic and diastolic strain impairment in AL patients lacking qualitative LGE enhancement.